Treatment of intractable pruritus in patients with cholestasis with molecular adsorbents recirculating system dialysis: a case series - Magdalena Antoszewska; Piotr Spychalski; Gerda Elisabeth Villadsen; Niels Kristian Muff Aagaard (Gastroenterology Review)
Pruritus commonly occurs in patients with cholestatic liver diseases. Pruritus that is refractory to pharmacological treatment may be an indication for liver transplantation [1–3]. Pathogenesis of hepatic pruritus is still not fully understood. However, it is probably associated with the accumulation of pruritogens in plasma and other tissues as a result of cholestasis [4] (bile salts, bile acids, progesterone metabolites, lysophosphatidic acid, endogenous opioids [1]).